Linder, T.; Barragan, P.; Mcnaughton, P. (Techniques Magazine, 2012)
The technical complexities of a jump or a throw presents field event coaches with unique challenges. If position, speed and force application are not synchronized, an athlete will perform poorly. The coach`s job is to help the athlete succeed, and this begins with a strong working relationship between coach and athlete. This relationship can be achieved through mutual respect, communication and clearly defined expectations and goals. This article tries to identify and clarify what a coach and athlete can do to enhance their working relationship during practice. The focus is on strategies that enhance the athlete`s ability to "feel" the movement in order to master it, which is referred to as perceptive intelligence. We have often wondered if we could coach efficiently without our five senses, particularly sight and hearing with both being so crucial to how we evaluate athletes on the field. For a coach, only two senses seem critic al: sight and hearing. An athlete, on the other hand, will deal with hundreds of sensory perceptions during their event. An athlete`s perceptive intelligence can have an immense impact on the outcome of a performance. Contents: - Communication and Technical Execution, - Efficient technical practices, - Rhythm, - Differences between Practice and Competition - How video technology can aid performance. Conclusion: Field events are arguably the most technically challenging in all of track & field, not only for the athlete but for the coach as well. The ability of the coach to observe and provide meaningful feedback in appropriate doses, while at the same time helping the athlete to focus on the tasks and goals at hand are the keys to success. Being mindful of the experience level and processing skills of the athlete will help you achieve that success quicker.